Adelie penguin banding data 1994-2021 from the California Avian Data Center hosted by Point Reyes Bird Observatory Conservation Science - Ballard, Grant (U.S. Antarctic Program (USAP) Data Center, 2021)
This project is an international collaborative investigation of geographic structuring, founding of new colonies, and population change of Adelie penguins (Pygoscelis adelia) nesting on Ross and Beaufort islands, Antarctica. This ongoing study will continue to consider the relative importance of resources that constrain or enhance colony growth (nesting habitat, access to food); the aspects of natural history that are affected by exploitative or interference competition among neighboring colonies (breeding success, foraging effort); climatic factors that influence the latter, especially sea ice patterns; and behavioral mechanisms that influence colony growth as a function of initial size and location (emigration, immigration). The research includes a census of known-age penguins, studies of foraging effort and overlap among colonies; and identification of the location of molting and wintering areas.